Impact of tillage on soil bio-chemical properties, water storage and environment - BHATT, RAJAN; ARORA, SANJAY (Journal of Soil and Water Conservation, 2021)
Tillage practices can affect soil properties and environment dynamically in space and time depending on its intensity. This literature review addresses the quantitative effects of soil tillage and associated management (e.g., crop residues) on the temporal and spatial variability of soil properties and finally on to the environment. Among different tillage options viz. conventional (CT), minimum (MT) and zero tillage (ZT)-their effects on the soil properties and environment varied. Therefore, the choice of any tillage system is too critical for mitigating adverse effect on the environment along with improving the livelihoods of the farmers. However, tillage effects on soil properties depends on the site-specific biophysical environment such as soil texture, prevailing climate variations, site characteristics, period of adoption, seasonal variability in rainfall, inherent soil fertility status. This review is compiled to come out with a perfect intermediate tillage system which ultimately leads to the sustainable agriculture. Therefore, some new farmer friendly intermediate tillage system with higher adaptation rate must be invented for practising the sustainable agriculture in the region. This further helped to mitigate the adverse effects of the global warming and declining soil chemical-biological soil health and finally to improve the environment.